THE ROLE OF TUMOR NECROSIS FACTOR-α G–308A, INTERLEUKIN-1β C–511T AND INTERLEUKIN-10 G–1082A GENE POLYMORPHISMS IN THE DEVELOPMENT OF SLOWLYRESOLVED COURSE OF COMMUNITY-ACQUIRED PNEUMONIA - V. I. Sovalkin; Ye. G. Pomorgaylo; O. N. Sabitova; Ye. P. Podgurskaya (Бюллетень сибирской медицины)
Purpose: To study the distribution of genotypes and alleles tumor necrosis factor-α G–308A, interleukin1β C–511T, interleukin-10 G–1082A in patients with slowlyresolved pneumonia and their association with clinical and radiologicalfeatures of the disease.Materials and Methods: We investigated 89 patients with community-acquired pneumonia, of which 37 people had a slowlyresolving course of the disease.The genotype distribution of studied polymorpisms corresponded the Hardy–Weinberg equilibrium.Results: We determined that the tumor necrosis factor-α G–308A and interleukin-10 G–1082A gene polymorphisms were associated with the long course of pneumonia. Slow resolution of the disease in patients who are carriers of GA and AA genotypes of tumor necrosis factor-α contributed to a severe course. The intensity of inflammation in these patients was reflected in the high rates of erythrocyte sedimentation rate and C-reactive protein. Prolonged duration in patients who are carriers of GG genotype of IL-10 was associated with significant clinical and laboratory manifestations at onset of the disease and more frequent development of pleural effusion. The frequencies of alleles and genotypes of interleukin-1β in observed patients did not differ. Conclusions: The data can be used for prognosis of slowlyresolved pneumonia